MINIMALLY INVASIVE INTERVENTIONS FOR LOWER LIMB VARICOSITY - Lyakhovskyi, V.I.; Borkunov, A.L.; Demyanyuk, D.G.; Sapun, L.V.; Lyakhovska, T.U.; Kravziv, M.I. (World of Medicine and Biology, 2012)
537 persons were operated about varicose veins at the Department of Vascular Surgery of the Poltava Regional Clinical Hospital. NV Sklifosovsky from 2009 to 2011. Minimally invasive interventions were performed for 152 (28.3%) patients. 32 men were(21.1%), women were 120 (78.9%) among them. The age of patients was 42,4 ± 3,1 years on average. They suffered from varicose veins of the lower limbs for 5-11 years. All patients were performed ultrasound color angioscanning of lower extremities. Data for ultrasound color angioscanning installed the main reasons of course and progression of varicose veins, allowed the ability to perform minimally invasive treatments for varicose superficial veins of the lower extremities. All patients were operated on. Access to the veins were made through small incisions. The following complications were observed in the early postoperative period: large subcutaneous hematoma, paresthesia, shins swelling, calf vein thrombosis, the spread of thrombotic process with the calf veins to the popliteal ones and saphenous vein thrombophlebitis. Most patients were discharged from the hospital in 3-4 days after surgery. Patients with symptoms of the great saphenous vein thrombophlebitis and deep vein thrombosis were discharged from the hospital after the "therapeutic window" in terms of the INR (2.0 - 3.0). Long-term results of treatment in a year after surgery were observed in 128 (84.2%) individuals. The good results of treatment were achieved in 114 (89.1%), satisfactory – in 14 (10.9%) patients.
Keywords: varicose disease; ultrasound diagnosis; minimally invasive interventions